THE ROLE OF AFLIBERCEPT IN THE TREATMENT OF A PATIENT WITH POLYPOIDAL CHOROIDAL VASCULOPATHY - CASE REPORT - Sekerinov, Natasa Trpevska; Nivichka Kjaeva, Jana; Pandilov, Stefan; Gjoshevska Dashtevska, Emilija; Petrusevska, Andrijana (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
To present a patient with polypoidal choroidal vasculopathy, an entity often overlooked and misdiagnosed in daily clinical practice. A 73-year-old patient with reduced visual acuity in the left eye was evaluated with a complete ophthalmological examination, fundus photography, optical coherence tomography of the posterior segment of the eye, and optical coherence tomography with angiography and a diagnosis of polypoidal choroidal vasculopathy with development of a type 1 choroidal neovascular network (aneurysmal-polypoidal network) was made. The changes shown on OCT referred to the presence of subretinal fluid, PED in the shape of the letter M, the presence of a "double layer sign" from the developed neovascular network in the form of a renal glomerulus. After application of an anti-VEGF preparation (Aflibercept) for a period of six months (five applied doses, three consecutive, and two every two months) there was regression of the lesion and improvement of visual acuity from 0.5 to 0.9 according to the Snellen optotype.  The characteristic changes of OCT and OCT-A, as well as the course of the disease corresponded with the literature data that we consulted during the evaluation of this case, thus the diagnosis of polypoidal choroidal vasculopathy was confirmed. Timely recognition of this not so rare entity is of great importance for appropriate management and treatment of the affected patient. Keywords: polypoidal choroidal vasculopathy, subretinal fluid, choroidal neovascular membrane, aflibercept